Influencia del Ambiente de Trabajo en los Trabajadores en la Industria Cárnica - Vega Torres, Agustín; Pérez González, Aurora (Ingeniería, 2001)
In order to determine the work environment on the workers, it has been studied a specific case of the meat industry. From the study, it has been found a lot of workers declaration front to different working situations, affecting their labor and family life. It has been found labor stress states, according to the factor and studied environment. There are situations related to the working requirements, job satisfaction, autonomous decisions, management stile, monotony, and if they are taking on account for the decisions they are affected on their work. Having on account the showed results they are affected by such situations, it is necessary to establish company politics tending to eliminate or to minimize the effects, through changes on the way the chiefs are related to their subordinates.